Kandungan Protein, Lemak dan Air Daging Bagian Brisket Sapi Brahman Cross yang Direndam dengan Ekstrak Nanas (Ananas comosus L. Merr) - Dara Surtina; Friza Elinda; Willa Yuliana (Jurnal Peternakan Mahaputra, 2021)
This study aims to determine protein content, fat content and water content of brisket meat from Brahman Cross beef soaked with pineapple extract at different times. This research has been carried out at the Laboratory of Animal Products Technology, Faculty of Animal Husbandry, Andalas University, Padang. The material used in thisstudy was Brahman Cross beef brisket section aged 5 years which was taken at the Bandar Pandung Slaughterhouse, Solok City. The study was conducted experimentally in the laboratory with 4 treatments and 4 replications with different soaking times, namely without soaking, soaking brisket meat with pineapple extract for 15 minutes, 30 minutes and 45 minutes. The observed variables were the protein, fat and water content of Brahman Cross beef brisket. The results showed that the average protein content of meat ranged from 14.78 – 17.69%, meat fat content 1.75 – 2.76% and meat water content 76.97 – 79.19%. From the results of the study, it was concluded that the Brahman Cross beef brisket meat which was soaked with pineapple extract at different times gave very significant differences in proteincontent (P < 0.01) and not significant differences in fat and water content.